The Hutterites in North America - Hostetler, John A. (New York Holt, Rinehart and Winston, 1967)
The authors describe in intimate detail the day-to-day living patterns of the Hutterites, a communal group living in the Great Plains of the United States and Canada. This personalistic treatment of the materials allows the reader to empathize fully with the Hutterites as persons.
Keywords: Culture